Oxytocin Reverses Osteoporosis in a Sex-Dependent Manner - Beranger, Guillaume E.; Djedaini, Mansour; Battaglia, Séverine; Roux, Christian H.; Scheideler, Marcel; Heymann, Dominique; Amri, Ez-Zoubir; Pisani, Didier F. (Frontiers in Endocrinology, 2015)
The increase of life expectancy has led to the increase of age-related diseases such as osteoporosis. Osteoporosis is characterized by bone weakening promoting the occurrence of fractures with defective bone regeneration. Men aged over 50 have a prevalence for osteoporosis of 20% which is related to a decline in sex hormones occurring during andropause or surgical orchidectomy. As we previously demonstrated in a mouse model for menopause in women that treatment with the neurohypophyseal peptide hormone oxytocin (OT) normalizes body weight and prevents the development of osteoporosis, herein we addressed the effects of OT in male osteoporosis. Thus, we treated orchidectomized mice, an animal model suitable for the study of male osteoporosis, for 8 weeks with OT and then analyzed trabecular and cortical bone parameters as well as fat mass using micro-computed tomography. Orchidectomized mice displayed severe bone loss, muscle atrophy accompanied by fat mass gain as expected in andropause. Interestingly, OT treatment in male mice normalized fat mass as it did in female mice. However, although OT treatment led to a normalization of bone parameters in ovariectomized mice, this did not happen in orchidectomized mice. Moreover, loss of muscle mass was not reversed in orchidectomized mice upon OT treatment. All of these observations indicate that OT acts on fat physiology in both sexes, but in a sex specific manner with regard to bone physiology.